Peran Ulama dalam Pendidikan Islam dan Implementasi Hukum Syariah di Era Digital - Afifah Novi Pujianingrum; Sri Katiwi; Amalia Khoirunisa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The digital era brings new challenges for ulama in teaching Islamic education and sharia law to the community. This article discusses the strategic role of ulama in utilizing digital technology to effectively spread Islamic values ​​and sharia law. This study also includes an analysis of the positive and negative impacts of the digital era on the implementation of sharia law.